การสร้างสื่อภาพนูนอักษรจีนเพื่อเสริมจินตภาพในทักษะการสื่อสารภาษาจีนเบื้องต้น สำหรับนักเรียนผู้พิการทางสายตา - ตั้งภากรณ์ บัณศิกาญจ (Journal of Education Studies, Chulalongkorn University, 2019)
The objectives of this research were to create Chinese alphabetical characters with convex form for visually impaired students based on the quality and criteria of 75/75 standard, and study their opinions of the character convex form. The research population consisted of student groups with visually impaired pupils at an efficiency development center and the Lampang Educational School for the Blind School. The research purposive sampling was comprised of 25 visually impaired students who were able to read braille and were ready to learn a foreign language consisting of group study and an occupational training group. The research tools utilized in this study were Chinese alphabetical characters with convex form, a quality assessment from the experts, and an achievement test after using Chinese characters with convex form. The data were analyzed by mean and standard deviation. The research result showed that Chinese characters with convex form created for visually impaired students indicated a higher efficiency index of 75.40/ 87.20. In addition, the opinion level of visually impaired students on Chinese characters with convex form to supplement imagination in an introduction to Chinese communication skills was the highest at an average of 4.82.